PKM—Penerapan Sistem Penerangan Panel Surya untuk Peningkatan Aktivitas Peternak Sapi di Desa Curah Temu Kec. Kota Anyar Kab. Probolinggo - Ilmirrizki Imaduddin; Muhammad Hasan Basri; Royan Wahyu Pratama; Moh Noval Fikri Ramdani; Fajar Sodeq (CV. Akira Java Bulu, 2024)
Abstract.CurahTemu Village, TegalPao Hamlet, Kota Anyar District, Probolinggo Regency, is one of the villages that lacks PLN electricity sources. The main potential of this village is agriculture and cattle farming such as feeding, cleaning cages, smoking cows which are only done in the area in the afternoon before the sun gets dark. The problem is when smoking along the road there is no lighting and there is no PLN electricity network. In this product, Community Service based on lighting from Solar Panels will be installed and installed. This PLTS system has solar energy with a capacity of 200 WP Panel and 100AH ​​battery with a load of 12Watt lights as many as 4 with a location in the cage, and a load of lights for the road 50Watt, efficiency 80%, total can be operated 12.5 Hours.